On Network Reliability Evaluation by Monte Carlo Method Using High-Performance Computing - Migov, D. A.; Weins, D. V. (Lobachevskii journal of mathematics, 2023)
The paper considers the NP-hard problem of calculation the reliability of a network, which elements are subject to accidental failures. As network reliability, we mean the probabilistic connectivity of a random graph with unreliable edges. To evaluate the reliability of a network, a parallel Monte Carlo method is used, improved by checking the connectivity of a particular graph realization simultaneously with the generation of this realization. Based of multi-agent simulation, we study the scalability of this algorithm and tune the parameters for an execution using high-performance supercomputers.